HBR's 10 must reads 2019 : The definitive management ideas of the year from Harvard business review
We've combed through the ideas, insights, and best practices from the past year of Harvard Business Review to help you get up to speed fast on the relevant ideas driving business today. Discover new ideas and sample the work from our vast cabinet of experts and their smart management thinking. Revisit these topics now to make sure you're incorporating the brightest, most up-to-date practices in your organization, or keep it as a reference to access these memorable pieces when you need them most. The collection includes articles on leadership, strategy, and innovation, as well as content to help you manage yourself and others. A year's worth of management wisdom, all in one place